ETR 300 : Quail Agro Farm / Nazia Marin ... [et al.] - Marin, Nazia; Amir, Mazuin; Kasmat, Norashikin (2010)
Agriculture is a part of science and industry where it is including the process of plant and animals growth for human use. In general, the agriculture sector consisting the cultivation of the soil, growing and harvesting crops, breeding and raising livestock and forestry. However, the farming sector is a part from the agriculture branches besides the harvesting of basic food, fruits and etc. Farming sector is one of the branches of agriculture other basic food crops, fruits, fisheries and aquaculture. All the listed branches of agriculture are in general has contributing to the basis of the Malaysian economy in the era after the independence by increasing the Gross Domestic Product (GDP). However, a drastic change of government towards making Malaysia a major HALAL food producer in the world and the implementation of security food security in the country and encouraged more food production in national culture based on maximizing their product. Therefore, the small and medium entrepreneurs who start with the 'first step' to run any kind of businessas well as improving skills and standards of living, especially for those with low income.